Предмет: Алгебра,
автор: kammak654321
(m+1-1/1- m):(1-2a-3b/2a+3b)
Ответы
Автор ответа:
0
(m+1-1/1- m):(1-2a-3b/2a+3b)=
(m /1- m) : (1-(2a+3b) / 2a+3b)=
(m /m(1/m - 1) : (2a+3b)(1/(2a+3b)-1) / (2a+3b)=
1 /(1/m - 1) : (1/(2a+3b)-1) =
1 /(1/m - 1)(1/(2a+3b)-1)
(m /1- m) : (1-(2a+3b) / 2a+3b)=
(m /m(1/m - 1) : (2a+3b)(1/(2a+3b)-1) / (2a+3b)=
1 /(1/m - 1) : (1/(2a+3b)-1) =
1 /(1/m - 1)(1/(2a+3b)-1)
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Другие предметы,
автор: Sonichkaa34
Предмет: Математика,
автор: nusup08
Предмет: Геометрия,
автор: m1sak
Предмет: История,
автор: Svetlyachok12Ilya